Air Filtration System Utilizing Biomimetic Technology and IoT for Air Quality Improvement - Fauzan, Mochamad Rizal; Al Azhima, Silmi Ath Thahirah; Pramudita, Resa; Hakim, Dadang Lukman; Rahmawati, Hanifah Indah; Azmi, Mutiara Nabila; Fauzi, Rafi Rahman; Somantri, Maman; Rahayu, Sri (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2024)
The